Embeddings of weighted Sobolev classes on a John domain - Vasil’eva, Anastasia A. (Eurasian Mathematical Journal, 2014)
In this paper, embedding theorems for weighted Sobolev classes are obtained. Here weights are functions of distance to some h-set.